Prarancangan Pabrik Biodiesel Dari Minyak Jarak Pagar dan Metanol Kapasitas 40.000 Ton/Tahun - Mawardi, Ahmad Kharis, Dr. Ir. H. Ahmad M. Fuadi, M.T, Ir. Nur Hidayati, M.T., Ph.D (2016)
in 2005 Indonesia has become a net oil importer. The increase in world crude oil prices have a large impact on the national economy. The advance of industrial development would sooner spend fossil fuels, therefore, one way of handling energy problems is to develop alternative energy sources. In addition to the reasons the depletion of fossil fuel resources, more important reason is to reduce damage to the environment. Solutions to overcome the dependency on fossil fuels is by establishing biodiesel from castor oil and methanol with a capacity of 40,000 tonnes per year is planned to be in operation for 330 days per year. The process of making biodiesel from castor oil and methanol, made through the transesterification process flow in a stirred tank reactor (RATB). In the reactor the reaction at liquid-liquid phase at a temperature of 600C bait, a pressure of 1 atm and resulted in a conversion of 98%. The condition of the plant is classified as low-risk plant operating conditions at atmospheric pressure. The formation process of jatropha oil into methyl ester initially castor oil reacted with methanol and will produce diglycerides and methyl ester, then the results diglycerides react with the alcohol molecules other and will generate monoglycerides and methyl esters and results of monoglycerides react with alcohols third would produce glycerol and methyl ester. Castor oil needs of at this plant as much 9670.1091 kg per hour and needs as much methanol 2099.6104 kg per hour. And the methyl ester product as 9519.6763 kg per day. This factory will be established in Boyolali area and fixed capital of Rp. 182,260,561,096.57 and working capital of Rp.150195.466.062.398,95. From an economic analysis of this plant show a profit before tax of Rp. 185,868,591,457.09 per year after taxes 30% profit reached Rp. 130.108.014.019,96 per year. Percent Return On Investment (ROI) before tax after tax 41.18% and 29.40%. Pay Out Time (POT) before taxes for 2.23 years and 2.9 years after tax. Break Even Point (BEP) amounted to 55.74%, Shut Down Point (SDP) amounted to 29.83%, Discounted Cash Flow (DCF) accounted for 33.56%. From the results of which get concluded, that the plant is profitable and feasible to set.